Penerapan Kain Kain Songket Palembang dan Sashiko pada Busana Modest Fashion - Fatmawati, Yuni Zhaafira; Indarti, Indarti (BAJU: Journal of Fashion and Textile Design Unesa, 2024)
Abstract The aim of this research is to determine the process and results of applying Palembang songket and sashiko embroidery to modest fashion. Palembang songket is a form of original Indonesian cultural heritage, combined with sashiko which is original Japanese culture. The implementation of this project was carried out using the double diamond method. The process of applying Palembang songket and sashiko to modest fashion clothing went through several phases. In the discover phase, the author conducted trend research, namely ITF 2024 with the Fusion theme and Borderless sub-theme. Next, in the define phase, the author determines the source of the idea for the burgundy clematis flower, which has meaning as a symbol of protection from evil and good luck. In the Develop phase, the author carried out design development, selecting designs, colors and songket patterns which were realized in modest fashion clothing. At the Deliver stage, the author created clothing by going through several discussions and evaluations. The result was that the application of Palembang songket and sashiko to modest fashion clothing is in accordance with the plan, including women's clothing consisting of 3 parts, namely a dress with a full circle skirt, an outer and a layer that used sashiko embroider that can be removed and reused. Men's clothing consists of a suit which used a combination of plain and songket fabric. Keywords: Songket Palembang, sashiko, modest fashion